PSYCHOLOGICAL FEATURES OF DEVELOPING SELF-MANAGEMENT SKILLS IN STUDENT YOUTH CHARACTERISTICS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article discusses the psychological characteristics of developing self-management skills in student youth, and provides detailed information about the importance of self-management in the educational process, knowledge acquisition, and finding one's place in society.